Del aprender a aprender al aprender a pensar: la variable funcional de la educación - Aznar Minguet, Pilar (Teoría de la Educación. Revista Interuniversitaria, 2009)
This paper focuses on the functional variable of educational content with an aim to analysing the incidence of said variable on the learning process and at the same time offer guidelines for its integration within the curricula. The question has been approached from a constructivist perspective, clearly revealing that learning to think requires the assimilation of metacognitive strategies and abilities regarding the processes of social interaction. Cognition, with affective and behaviour-related aspects composing its central core, is regarded as being the driving force behind said processes. The diadic relationships which occur within these processes affect all of those involved -teachers and pupils- creating a set series of responsibilities as regards establishing a relevant integration of «what» and «how» to teach and learn, a question which leads to an analysis of the double perspective from which said integration can be facilitated: - from the perspective of educational action, based on the «help» -conceptional and operational scaffolding- supplied by the teacher. - from the perspective of educational activity, based on the actions and operations carried out by the individual during his process of learning. In the of both perspectives, process «standards» are offered together with a compendium of educational techniques directed towards implementing three key aspects: the self-adjustment of learning, the construction of «meanings» and the «profound» processing of information.